2022
DOI: 10.1038/s41467-022-33911-8
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of TMPRSS2 in SARS-CoV-2 infection in murine airways

Abstract: In cultured cells, SARS-CoV-2 infects cells via multiple pathways using different host proteases. Recent studies have shown that the furin and TMPRSS2 (furin/TMPRSS2)-dependent pathway plays a minor role in infection of the Omicron variant. Here, we confirm that Omicron uses the furin/TMPRSS2-dependent pathway inefficiently and enters cells mainly using the cathepsin-dependent endocytosis pathway in TMPRSS2-expressing VeroE6/TMPRSS2 and Calu-3 cells. This is the case despite efficient cleavage of the spike pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 44 publications
7
45
0
Order By: Relevance
“…Briefly, reliable evidence has been provided that the Omicron sublineages, other than replicating prevalently in the upper respiratory tract [ 12 ], may also penetrate the host cell by endocytosis and sorting within endolysosomes, employing an acid-activated cathepsin L mechanism [ 13 ]. This evidence has been recently confirmed by an elegant study published by Iwata–Yoshikawa et al [ 14 ], who showed that Omicron sublineages seem to use the furin/TMPRSS2-dependent entrance pathway less efficiently, thus penetrating the host cells prevalently through a cathepsin-dependent endocytosis pathway in TMPRSS2-expressing cells. Cell to cell transmission is a third important mechanism that has been elucidated for explaining host cell penetration by SARS-CoV-2, whereby endosomal membrane fusion [ 15 ] or generation of syncytia mediated by the binding of spike protein expressed on the surface of infected cells with ACE2 present in adjacent and uninfected cells [ 16 ] may allow the spread of the virus in the nearby respiratory tissue.…”
Section: Pathways Of Host Cell Penetration By Sars-cov-2mentioning
confidence: 68%
“…Briefly, reliable evidence has been provided that the Omicron sublineages, other than replicating prevalently in the upper respiratory tract [ 12 ], may also penetrate the host cell by endocytosis and sorting within endolysosomes, employing an acid-activated cathepsin L mechanism [ 13 ]. This evidence has been recently confirmed by an elegant study published by Iwata–Yoshikawa et al [ 14 ], who showed that Omicron sublineages seem to use the furin/TMPRSS2-dependent entrance pathway less efficiently, thus penetrating the host cells prevalently through a cathepsin-dependent endocytosis pathway in TMPRSS2-expressing cells. Cell to cell transmission is a third important mechanism that has been elucidated for explaining host cell penetration by SARS-CoV-2, whereby endosomal membrane fusion [ 15 ] or generation of syncytia mediated by the binding of spike protein expressed on the surface of infected cells with ACE2 present in adjacent and uninfected cells [ 16 ] may allow the spread of the virus in the nearby respiratory tissue.…”
Section: Pathways Of Host Cell Penetration By Sars-cov-2mentioning
confidence: 68%
“…5 B and C), suggesting that alimemazine inhibits SARS2-S-mediated cell entry through a mechanism similar to that used by the DRD2 antagonists. The serine protease TMPRSS2 plays a critical role in SARS-CoV-2 infection in vivo ( Iwata-Yoshikawa et al, 2022a ). We then assessed the inhibitory effect of alimemazine on VSV-based pseudovirus cell entry in Vero E6 cells expressing TMPRSS2 (VeroE6/TMPRSS2).…”
Section: Resultsmentioning
confidence: 99%
“…The BA.1 and BA.5 isolates used herein have 14 amino acid differences in the spike protein (Supplementary Table 3). Pathogenicity has been shown to be dependent on TMPRSS2 utilization 109 , with TMPRSS2 utilization reported to be a virulence determinant, even for omicron variants 110 . Treatment with a TMPRSS2 inhibitor also prevented brain infection in K18-hACE2 mice 111 .…”
Section: Discussionmentioning
confidence: 99%